ANALISIS KEBUTUHAN MODUL PEMBELAJARAN GEOMETRI ANALITIK BERBASIS MULTIREPRESENTASI - Erdyna Dwi Etika; Addin Zuhrotul ‘Aini (Jurnal Pembelajaran Matematika, 2018)
Abstract: The purposes of this research were: (1) Analyzing the implementation of analytical geometry learning at the Mathematics Education Department of STKIP PGRI Nganjuk; (2) Finding out lecturers’ needs of teaching materials that helped students improve students’ learning achievements; (3) Finding out students’ needs of teaching materials that helped students improve their creativity and learning achievement. This was a qualitative and descriptive research. The subjects in this research were chosen by using purposive sampling. The chosen subjects of this research were the sixth-semester students at the Mathematics Education Department of STKIP PGRI Nganjuk. Collecting data was performed by the researchers themselves by using observation sheets and questionnaires as the main and supporting instruments. Processing and analyzing data were performed in four steps: (1) coding data; (2) data tabulation; (3) qualitative data analysis; (4) interpretation of the results of the analysis. The researchers found that: (1) The implementation of analytical geometry learning in the mathematics education department still used the lecture and discussion methods meanwhile the used teaching materials were books which only emphasize on the material and solving the routine problems; (2) The lecturers needed modules as teaching materials that could help students improve learning outcomes and creativity in problem-solving; (3) 76% of students found difficulties in analytical geometry courses and 86% of students stated that the existing teaching materials did not make them completely understand and got motivated in learning so the students agreed with and supported the creation and development of multi-representation based of analytical geometry learning modules.Keywords: Analytical Geometry, Analysis of Needs, Module, Multi-Representation.